Centre-periphery model explaining the regional development of the informational and transitional society - Garri Raagmaa (European Regional Science Association (ERSA), 2003)
This paper analyses regional development and uses centre-periphery models (CPM) of Friedmann, Gibbs and Hautamäki as a base for theoretical discussion. In general, these centre-periphery models foresee stabilisation and de-concentration of population and economic agents after the concentration stages. The spatial processes of 1970s and 1980s were rather well described by the CPM. However, the 1990s turned to a new concentration in several countries. Classical CPM that assumed the continuity of industrial society and relevant factors, both negative and positive for concentration, influencing regional structures and settlement became useless. Therefore, first topic in this paper analyses concentration-deconcentration factors of the informational society and tries to plant the classical approach in the new soil. Secondly, we set a hypothesis arguing that Baltic Countries have followed partly similar, but simultaneously rather different spatial development stages. If the Western economies enjoyed particularly after the World War II economic and political stability, then regional development of their Eastern counterparts has been influenced by several political convulsions. Besides, even the same results in urban development may have had rather different causes in the West and former East. The empirical part analyses the regional development of Estonia in a historic perspective. The description of past developments attempts to outline (1) influencial causal factors, (2) periods of concentration and deconcentration, and (3) particularities compared with Western countries. The discussion is supported mainly by population data of past censuses, but uses also a limited number of soft empirical materials like small case studies, interviews and observations. Finally, we attempt to design a comparison of different urban development stages in UK, Finland and Estonia. This paper prepares and tests an extensive analyse of census and labour market survey as well as enterprise development data of the transition period, the 1990s. Key words: centre-periphery model, urban development stages, political factors in urban development
Keywords: 330